Oxygen-insensitive synthesis of the photosynthetic membranes of Rhodobacter sphaeroides: a mutant histidine kinase. - Eraso, J M (1995)
Two new loci, prrB and prrC, involved in the positive regulation of photosynthesis gene expression in response to anaerobiosis, have been identified in Rhodobacter sphaeroides. prrB encodes a sensor histidine kinase that is responsive to the removal of oxygen and functions through the response regulator PrrA. Inactivation of prrB results in a substantial reduction of photosynthetic spectral complexes as well as in the inability of cells to grow photosynthetically at low to medium light intensities. Together, prrB and prrA provide the major signal involved in synthesis of the specialized intracytoplasmic membrane (ICM), harboring components essential to the light reactions of photosynthesis. Previously, J. K. Lee and S. Kaplan (J. Bacteriol. 174:1158-1171, 1992) identified a mutant which resulted in high-level expression of the puc operon, encoding the apoproteins giving rise to the B800-850 spectral complex, in the presence of oxygen as well as in the synthesis of the ICM under conditions of high oxygenation. This mutation is shown to reside in prrB, resulting in a leucine-to-proline change at position 78 in mutant PrrB (PRRB78). Measurements of mRNA levels in cells containing the prrB78 mutation support the idea that prrB is a global regulator of photosynthesis gene expression. Two additional mutants, PRRB1 and PRRB2, which make two truncated forms of the PrrB protein, possess substantially reduced amounts of spectral complexes. Although the precise role of prrC remains to be determined, evidence suggests that it too is involved in the regulatory cascade involving prrB and prrA. The genetic organization of the photosynthesis response regulatory (PRR) region is discussed.